A rapid pre-implementation evaluation to inform a family engagement navigator program during COVID-19 - Taylor, Stephanie Parks (Implement Sci Commun, 2020)
BACKGROUND: Innovative models of family engagement and support are needed in the intensive care unit (ICU) during times of restricted visitation such as the COVID-19 pandemic. Limited understanding of the factors affecting the uptake and outcomes of different family support models hinders the implementation of best practices. We aimed to conduct a rapid pre-implementation evaluation of stakeholder-perceived facilitators and barriers to design implementation strategies to support a novel program using medical students to facilitate family-centered care in the ICU. METHODS: We conducted a 2-step process. In step 1, we gathered contextual data via interview-style open-ended questions sent to clinicians and navigator stakeholders via email. We used electronic data collection due to the physical distancing requirements, the need to prioritize brief data collection for respondent burden, and the need for rapid knowledge gain. A codebook based on the Consolidated Framework for Implementation Research (CFIR), an integrated framework from the field of implementation science, was used to analyze the findings. In step 2, a pilot of the intervention was implemented with 3 navigators over 2 weeks. Implementation strategies were developed to target barriers identified by the pre-implementation evaluation. RESULTS: Fourteen (70%) of the identified stakeholders responded to the survey. Ten constructs encompassing all five CFIR domains were present in responses as implementation influencers, with the Intervention domain most frequently represented. Through these results and operational feedback from navigators during the pilot period, stakeholders selected multiple implementation strategies: audit and provide feedback, develop educational materials, conduct ongoing training, promote adaptability, assess and redesign workflow, identify and prepare champions, and engage community resources. CONCLUSIONS: We demonstrated how a conceptually based pre-implementation program evaluation can be used to rapidly inform optimal implementation strategies. We report key factors to inform design and implementation strategies for a novel ICU family engagement navigator program that may be useful to others wishing to adopt similar programs. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s43058-020-00098-2.